2001
DOI: 10.1177/014107680109401010
|View full text |Cite
|
Sign up to set email alerts
|

Primary Pulmonary Hypertension in Pregnancy

Abstract: Probably the Lippes loop had been inserted about 23 years previously after a miscarriage. Since her encephalitis no one had been prepared to do a pelvic examination or had attempted a cervical smear, because of her abusiveness. Analysis of the stone showed it to consist of calcium carbapatite (calcium carbonate and phosphate).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 6 publications
0
15
0
Order By: Relevance
“…Postoperative increases in peripheral vascular resistance occur and may contribute to post-partum mortality. 21 Although there may be less alteration to hemodynamic parameters with regional anesthesia, good outcomes have been reported with both regional and general anesthesia [1][2][3][4][22][23][24] Little has been written about the effects of epoprostenol on the intrauterine environment. In our case, intensive fetal surveillance during intravenous epoprostenol therapy failed to show fetal harm.…”
Section: Discussionmentioning
confidence: 99%
“…Postoperative increases in peripheral vascular resistance occur and may contribute to post-partum mortality. 21 Although there may be less alteration to hemodynamic parameters with regional anesthesia, good outcomes have been reported with both regional and general anesthesia [1][2][3][4][22][23][24] Little has been written about the effects of epoprostenol on the intrauterine environment. In our case, intensive fetal surveillance during intravenous epoprostenol therapy failed to show fetal harm.…”
Section: Discussionmentioning
confidence: 99%
“…In patients with primary pulmonary hypertension, PGI2 acutely decreases pulmonary vascular resistance, increases cardiac output and increases systemic oxygen delivery. 17,20,[24][25][26][27][28][29][30][31][32][33][34][35][36][37][38] Elliot et al 30 used nebulized iloprost therapy as early as 8 weeks in pregnancy, with pregnancies completed between 25 and 36 weeks, and with deliveries by caesarean section under local anesthesia without maternal or infant mortality or congenital abnormalities. In patients with congenital heart disease and PAH who failed conventional therapy, long-term, continuous intravenous PGI2 reduced pulmonary artery pressures by 21%, improved cardiac index (69%), pulmonary vascular resistance (52%), and New York Heart Association functional class, but not 6-minute walk distance.…”
Section: Prostacyclin Pathwaymentioning
confidence: 99%
“…Most authors reported positive outcomes with the use of epoprostenol [16][17][18][19][20]. Less data is available for nitric oxide [21], sildenafil [22,23], iloprost [24], and nebulized iloprost combined with epoprostenol [16,25]. A recent study has shown that 52% of pregnant women with CHD-PAH received PAH-specific therapy [7].…”
Section: Specific Therapies For Pulmonary Arterial Hypertension In Prmentioning
confidence: 99%